A Dona Pé de Cabra: review and editing of a manuscript testimony (Filologia e Linguística Portuguesa, 2023)
The purpose of this article is to investigate the process of transmission of the text A Dona Pé de Cabra, present in lineage books. We expose, in this work, the result of the review related to the direct tradition of this text, which is composed, until now, of fourteen testimonies: eleven manuscripts and three printed ones. This article gives news of what has been developed in the field of research for the preparation of a critical edition of this text. In order to illustrate the process of preparing testimonies for the collation phase, we also present a diplomatic edition, accompanied by a facsimile, of one of the manuscript testimonies: the one present in codex COD-977 of the Biblioteca Nacional de Portugal.